VALUASI EKONOMI DEGRADASI LAMUN DI TANJUNG TIRAM DESA POKA KOTA AMBON MELALUI PENDEKATAN CONTINGENT VALUATION METHOD - Giansun Aprilia Burhanudin; Eygner Gerald Talakua; Janer Sangaji; Angela Ruban (PAPALELE (Jurnal Penelitian Sosial Ekonomi Perikanan dan Kelautan), 2025)
In coastal areas there are 4 types of ecosystems which have an important role in the habitat of various biota in coastal areas, namely coral reef ecosystems, coastal ecosystems, seagrass ecosystems and mangrove ecosystems. Four ecosystems, the seagrass ecosystem is the least known. This is due to a lack of attention and lack of public knowledge of the seagrass ecosystem, so that the seagrass ecosystem is often misinterpreted as an environment that is useless and does not provide benefits to humans. Seagrass as a shallow marine ecosystem has an important role in supporting the life and development of species in shallow seas, namely as a primary producer, habitat for biota and trapping sediment and nutrients in the waters. One of the seagrass ecosystem locations that has high utilization pressure by people living in coastal areas is Teluk Ambon Dalam. The sustainability of the Teluk Ambon Dalam coastal ecosystem is threatened by physical destruction such as dredging of beach sand and sedimentation due to weak land management and pollution. This research obtained an economic valuation of seagrass degradation in Tanjung Tiram, Poka Village. This research aims to analyze the perceptions of coastal communities in Poka Village regarding seagrass degradation and estimate the value of seagrass degradation in Poka Village, Ambon, using the Contingent Valuation Method approach. Data analysis methods include perception analysis and willingness to pay analysis with this method. The results show that the coastal communities of Tanjung Tiram, Poka Village's perception of seagrass degradation is known or positive, proven by the average index value of 3.45. The total value of the willingness to pay the coastal community of Tanjung Tiram, Poka Village, for seagrass rehabilitation is IDR 903,314.24/month, showing the proxy/suspected or estimated value of seagrass degradation